A Rare Cause of Hypovolemic Shock in Prepubertal Girl: Vaginal Leech Infestation - W. Lahmini; M. Bourrous; K. Harou (Hindawi Limited, 2019)
Vaginal bleeding in girls is an alarming symptom for both parents and pediatricians. Serious underlying causes should be always evoked. Case Report. We describe here a 9-year-old girl who was admitted at our emergency department for vaginal bleeding and severe anemia. No history of trauma and no evidence of prior abuse were reported by the parents. Full Blood Count showed profound anemia (hemoglobin at 4 g/dl). The child was managed as a hypovolemic shock and resuscitated with intravenous fluids and urgent blood transfusion. Gynecologic examination found a live leech at the vulva and the extraction was facilitated by applying a saline solution. The child was clinically stable and discharged home the next day with ambulatory treatment. Conclusion. This case emphasizes that a through external genital exam with possible exam under anesthesia should be undertaken in all girls with unexplained vaginal bleeding and that in those living in rural areas without potable water, leech infection should be considered.